2020
DOI: 10.3390/info11100462
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technology (ICT) Governance Processes: A Case Study

Abstract: Information and Communication Technology (ICT) Governance is increasingly necessary and present in organizations aiming to improve the maturity of their ICT processes. This paper presents an analysis of the ICT Governance processes of a Brazilian Federal Public Administration agency. To assess the maturity of the ICT Governance processes, we surveyed and diagnosed the processes performed by the agency and organized a series of meetings/discussions to assist in the improvement and modeling of the processes rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…This work investigates three characteristics within environmental impact: competitive intensity, competitive pressure, and the bandwagon effect. Competitive intensity arises in conditions where competitors are abundant, and there are few opportunities for growth in the industry [68]. Ref.…”
Section: Environmental Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…This work investigates three characteristics within environmental impact: competitive intensity, competitive pressure, and the bandwagon effect. Competitive intensity arises in conditions where competitors are abundant, and there are few opportunities for growth in the industry [68]. Ref.…”
Section: Environmental Impactmentioning
confidence: 99%
“…Furthermore, [85] suggested that management researchers recognize the emerging vitality of SM use for organizations. They proposed that scholars focus on how SM allows organizations and researchers enlarge their investigations related to knowledge co-creation and performance [68].…”
Section: Social Media Adoption and Sme Performancementioning
confidence: 99%
“…Capital city is supposed to be livable and smart for its people [47]. Government institutions in the new capital city must employ ICT that could provide competitiveness for the governments where they must perform effective, efficient, and transparent services for the people [46,48,49]. ICT could also contribute to education, health, commerce, and the government sector.…”
Section: Geographic Centralitymentioning
confidence: 99%
“…During the past years, many entities have developed frameworks and models for IT governance, with the aim of assisting companies in implementing IT governance. Firms should design their IT process architecture in order to be able to use these frameworks and achieve the benefits expected from them (Dias Canedo et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%